Analiza dendrochronologiczna próbek drewna z wczesnośredniowiecznego grodziska w Płońsku, woj. mazowieckie - Smoliński, Antoni; Ważny, Tomasz (Acta Universitatis Lodziensis. Folia Archaeologica, 2011)
The objective of this article is to present the results of dendrochronological analyses of a complex of samples taken from an early medieval stronghold at Płońsk. Research excavations were conducted in the area of 19-go Stycznia Street (building of a sanitary collector), and adjoining to the stronghold in the western area (building of so-called little bypass of P³oñsk). In the area of 19-go Stycznia Street during the terrain works wooden structures of the stronghold`s rampart were found (box – crossed logs structure). Five samples were collected for the dendrochronological analysis from the excavated area, four of which gave positive results. The yearly dates 972–979 were obtained. Another area where dendrological samples were taken is connected with the building of a so-called bypass of Płońsk. Remains of a crossing connecting the stronghold with the adjoining settlement were recorded, as well as a pit in a form of a well (pit no. 41). 12 wood samples were taken from the crossing, from which dates in an interval 840–862 were obtained. Whereas, from pit 41 dates placed in an interval 919–954 were obtained. Although there is a detailed study on the findings of the excavation of the early medieval stronghold at Płońsk, the dendrochronological analyses results shed new light on the history of this almost unknown defensive structure, and, at the same time, on the history of Masovia. Dates obtained both from the samples taken from the crossing and pit 41 (862 and 953) indicate that in this place as early as in the 2nd half of the 9th century a close settlement spot (stronghold with an adjoining settlement?) existed. On the other hand, an analysis of samples from the rampart structures shows that in the 3rd quarter of the 10th century (979), further development of the existing structure – raising new ramparts, solidly made of selected material, with a construction typical of the strongholds of the early Piast period, that is box – crossed logs structure with the use of natural hooks took place.